Prevalence of occupational skin diseases among rice field workers in Haryana - ., Shiva; Singh, Sumitra; Singh, Shailendra Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: The objective of the study was to estimate the risk of occupational skin diseases among workers who were exposed to animal manure during rice cultivation in India. Methods: Questionnaire based six month follow up study with weekly assessment of skin diseases in rice field workers from village Dabra, in Haryana state of India who were exposed to animal manure was carried out among the agricultural workers working in rice field along with dermatological examination of exposed parts. Results: Out of total 574, workers, 90 were excluded as per exclusion criteria. 71 workers out of 370 workers who were free from diseases at baseline survey data develop a new disease with cumulative incidence of 19.1%. There was higher prevalence of dermatitis among all of reported skin diseases. Conclusions: Exposure to animal manure mixed with standing water is a major risk factor among the workers working in rice field and attempt should be made to identify the type of dermatitis and relate its causative agent with any specific biological or chemical agents present in animal manure mixed with standing water of rice field.